2000
DOI: 10.1038/sj.cgt.7700207
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human hematopoietic tumor formation by targeting a repressor Myb-KRAB to DNA

Abstract: In many hematopoietic malignancies, c-Myb, a nuclear transcription factor of hematopoietic cells, is an activated oncogene. To achieve a specific inhibition of hematopoietic tumor growth, an inducible fusion protein consisting of the Myb DNA binding domain (DBD) and the active repressor domain KRAB, the Krü ppel-associated box of the developmental zinc-finger protein KOX-1, was generated. The MybDBD-KRAB fusion protein is a potent repressor of Myb-induced gene expression from Myb-responsive reporter genes cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In a previous study, we detected ZNF217 overexpression in cell lines and different tissue specimens of ovarian cancer, finding that ZNF217 overexpression was highly related to ovarian cancer (26,27). In the present study, we used a plasmid-mediated RNAi method to obtain an efficient knockdown of ZNF217 gene.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a previous study, we detected ZNF217 overexpression in cell lines and different tissue specimens of ovarian cancer, finding that ZNF217 overexpression was highly related to ovarian cancer (26,27). In the present study, we used a plasmid-mediated RNAi method to obtain an efficient knockdown of ZNF217 gene.…”
Section: Discussionmentioning
confidence: 83%
“…Protein can pass through nuclear pores into the nucleus of the cell (25). Currently, more and more studies have shown that zinc finger protein family members play an important role in development process in varieties of cancers (26)(27)(28). ZNF217, one of the zinc finger protein family members, was demonstrated to encode alternatively spliced Kruppel-like transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic TAL DBDs (T-DBDs) can be appended at either their C-or N-termini with effector domains conferring function in mammalian cells -for example the KRAB repressor domain 15,23 . In both native and artificial TFs, KRAB domains recruit the KAP1 co-repressor and, in turn, endogenous enzymatic complexes that methylate histones and DNA and trigger focal heterochromatin formation [23][24][25][26][27][28] .…”
Section: Resultsmentioning
confidence: 99%
“…Although these genes may theoretically be involved in transcriptional activation or repression, all KRAB zinc finger genes studied so far have been shown to act only as transcriptional repressors (Margolin et al, 1994;Witzgall et al, 1994;Vissing et al, 1995). Accordingly, engineered chimeric fusion proteins consisting of KRAB domains combined with different DNA binding domains of oncogenic transcription factors have been shown to target their respective oncogene and specifically inhibit malignant growth and suppress tumorigenesis (Fredericks et al, 2000;Nawrath et al, 2000). As altered expression of such strong transcriptional repressors might well be the cause of tumor development, we have put effort not only to elucidate further the genomic structure of ZNF331 but also to extend our knowledge about the expression patterns of ZNF331.…”
Section: Discussionmentioning
confidence: 99%